Giant Cell Tumor of the Temporal Bone with Direct Invasion into the Middle Ear and Skull Base: A Case Report. (3rd April 2012) - Iizuka, Takashi; Furukawa, Masayuki; Ishii, Hisato; Kasai, Misato; Hayashi, Chieri; Arai, Hajime; Ikeda, Katsuhisa
Abstract : Giant cell tumor (GCT) is classified as a benign bone tumor, and it is frequently identified at the epiphysis of long bones and relatively rare in the temporal bone. For orthopedists expert at recognizing bone and soft tissue tumors, the diagnosis of GCT is relatively easy; however, since head and neck surgeons experience few cases of GCT, it may be difficult to diagnose when it occurs in the temporal bone. A 32-year-old man complained of left hearing loss, aural fullness, and tinnitus. Examination of the ear revealed a bulging tumor. Audiologic examination demonstrated conductive hearing loss of the left ear. Computer tomograph of the temporal bone showed a soft-tissue-density specification indicating bone destruction at the left temporal bone. The tumor invaded the skull base. Imaging examinations using magnetic resonance imaging revealed a nonhomogenous isosignal intensity area on T1 at the left temporal bone. After intravenous gadolinium, the mass showed unequal enhancement. This patient subsequently underwent surgery to remove the lesion using transmastoid and middle fossa approach. Pathological examinations from specimens of the tumor revealed characteristic of GCT. No clinical or radiological evidence of tumor recurrence was detected for 4 years.